Reservoir quality and flow unit characterization of a reservoir in X fieid, Baram Delta - Rahim, N.A. (American Scientific Publishers, 2020)
Reservoir stratigraphie continuity are uncertainties that may be due to lack of facies association definition in reservoirs. These uncertainties come into play where proper porosity-permeability (poroperm) evaluation is misrepresented, leading to volumetric estimation uncertainties. Most oil fields in the Baram Delta have been previously studied with the development of static models. The lack of sequence stratigraphie input in the study was due to constraints including fault shadowing and gas chimney presence which deterred the volume estimations. Earlier interpretation of fades distribution and depositional environment of a field, named X, was achieved mainly by using core descriptions and interpretations. In this study, a reinterpretation of the depositional environment and fades distribution were carried out in the R1 and R2 reservoirs. The analysis was done by incorporating the depositional environment and fades with newly interpreted fades comprising of sand, silty sand, sandy shale and shale fades, created using neural network programme. Utilising newly set fades definitions with additional inputs including porosity and permeability data, a better fades distribution for the reservoir is emplaced. With the fades definitions set for 3 wells, the reservoir quality was investigated through poroperm relationship, reservoir quality index (RQI) and fluid flow unit interpretation. The new definitions for reservoir fades consequently matched well to the core descriptions. The R1 reservoir facies-poroperm relationship were clustered well with respect to each fades type. The RQI was then evaluated from the permeability and porosity values for all the selected wells. The fluid flow units were estimated using depth interval difference, effective porosity and permeability data. The fluid flow regimes are different tor all the wells, where the updip Well B displayed significantly better flow capacity than both Well C and Well A. However, Well C also displayed good fluid flow capability, indicated by high gradient flow capacity over storage capacity, although with presence of some layers of poor flow quality. Good communication for the downdip wells provides a potential for lateral fluid flow component which can influence the storage and flow capacity of fluid in the updip Well A, and thus creating an overall control and validation of fluid capacity in the reservoir. Copyright Â© 2020 American Scientific Publishers All rights reserved